Effect of Al/Mg Ratio on the Microstructure and Phase Distribution of Zn-Al-Mg Coatings - Ziyue Zhang; Jie Zhang; Xingyuan Zhao; Xin Liu; Xuequn Cheng; Sheming Jiang; Qifu Zhang (Metals, 2023)
In contrast with studies such as those on the effect of a single elemental variable on Zn-Al-Mg coatings, Mg/Al is considered a variable parameter for evaluating the microstructure of Zn-Al-Mg coatings in this work, and the combined effect of the two elements is also taken into account. The Mg/Al ratios in the continuous hot-dip plating of low-alumina Zn-Al-Mg coatings were 0.63, 0.75, 1.00, 1.25, and 1.63. respectively, and the microstructures of the different coatings were observed using scanning electron microscopy (SEM). The surface elemental distributions of the coatings were analyzed with energy dispersive spectrometry (EDS) and X-ray diffraction (XRD) analysis to understand the phase distributions of the coatings, which mainly consisted of a zinc monomeric phase, a binary eutectic phase (Zn/MgZn2), and a ternary eutectic phase (Zn/Al/MgZn2). Statistical calculations of the phase distributions in colored SEM images were performed using ImageJ-win64 software, comparative analysis of the solidification simulation results was carried out with thermodynamic simulation software (PANDAT-2023), and evaluation of the corrosion resistance of the platings was performed using macroscopic cyclic immersion corrosion experiments. The results show that with the increase in the Mg/Al ratio, the binary eutectic phase in the coatings gradually increased, the variation trend of the ternary eutectic phase was not obvious, and the corrosion resistance of the coatings gradually improved.